2010
DOI: 10.1177/0269216310367536
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling informed consent and ‘do no harm’: ethical challenges in palliative-care research and practice in chronic obstructive pulmonary disease

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 20 publications
(23 reference statements)
0
22
0
1
Order By: Relevance
“…On the one hand, this might be a source of bias. On the other hand, it is well known that there is poor communication between clinicians and patients about the life-limiting nature of COPD and the terminal prognosis in advanced stages of the disease [42]. As "palliative care needs" are associated with mortality and death, we assume that patients would most probably deny them.…”
Section: Limitationsmentioning
confidence: 99%
“…On the one hand, this might be a source of bias. On the other hand, it is well known that there is poor communication between clinicians and patients about the life-limiting nature of COPD and the terminal prognosis in advanced stages of the disease [42]. As "palliative care needs" are associated with mortality and death, we assume that patients would most probably deny them.…”
Section: Limitationsmentioning
confidence: 99%
“…Laws protecting the rights and privacy of the public have led to restrictions on the use of personal data and this has had an impact on research design and, in particular, recruitment [10,13,14]. For instance, the identification of potential research participants is more challenging if researchers are only permitted to approach individuals who formally ‘opt in’ to a study, thereby signalling an active willingness to participate [10].…”
Section: Introductionmentioning
confidence: 99%
“…5,19,20 For example, researchers involved in a recent study conducted with a palliative care population argued that 'the requirements imposed by the ethics committee resulted in a research study where the highest standards of transparency of purpose and informed consent were compromised in the context of a wish to 'do not harm''' ( p. 471). 21 They identified that the heightened degree of protection and sensitivity afforded to palliative care patients can serve as a source of conflict between researchers, ethics committees, and health care practitioners. In a study conducted by Stevens et al 22 the researchers highlight the problems faced by research committees in reviewing palliative care research proposals; risks of harm or breaches of confidentiality and privacy are assumed to be likely to occur unless particular procedures are followed.…”
Section: Introductionmentioning
confidence: 99%